Recurrent uterine rupture during pregnancy: a case report and literature review - Bakavičiūtė, Greta; Melech, Amelija; Bužinskienė, Diana; Drąsutienė, Gražina; Poškus, Tomas (Lietuvos chirurgija, 2015)
Recurrent uterine rupture is a rare and dangerous obstetric complication for both the mother and the fetus, which is why it is important to surmise, identify and treat it urgently. The aim of this article is to present a case report of recurrent uterine rupture after previous cesarean section and review the literature regarding the incidence, risk factors, clinical findings and management.